ABCG2 Single Nucleotide Polymorphism Affects Imatinib Pharmacokinetics in Lower Alpha-1-Acid Glycoprotein Levels in Humans - Park, Jin-Woo; Chung, Hyewon; Kim, Kyoung-Ah; Kim, Jong-Min; Park, In-Hwan; Lee, Sangjin; Park, Ji-Young (Frontiers in Pharmacology, 2021)
Imatinib is transported extracellularly by ABCB1 and ABCG2 efflux transporters and bound to alpha-1-acid glycoprotein (AGP) in the bloodstream. However, the clinical and pharmacokinetic effects of ABCB1 and ABCG2 on imatinib were inconsistent in the previous literature and have not been confirmed. Therefore, in the present study, we explored the effects of the ABCG2 and ABCB1 genetic polymorphisms on imatinib pharmacokinetics in association with plasma AGP levels in healthy subjects. Twenty-seven healthy individuals were recruited, genotyped for ABCG2 and ABCB1, and given a single oral dose of 400 mg imatinib. Plasma imatinib concentrations were measured and its pharmacokinetics was assessed with respect to ABCG2 (c.421C>A and c.34G>A) and ABCB1 (c.1236C>T, c.2677C>T/A, and c.3435C>T) genotypes, and plasma AGP levels. AGP levels showed a strong positive correlation with imatinib pharmacokinetics. ABCG2 c.421C>A single nucleotide polymorphism showed a statistically significant effect on imatinib pharmacokinetics in low plasma AGP levels groups (<80 mg/dL); subjects with high plasma AGP levels (n=5, ≥80 mg/dL) were excluded. The results indicate that plasma AGP levels and ABCG2 polymorphisms modulated imatinib pharmacokinetics; however, the effects of the ABCG2 transporter was masked at high plasma AGP levels.